2016
DOI: 10.1080/15592324.2016.1183084
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides, micro- and macro-nutrients, limonoids, flavonoids, and hydroxycinnamates composition in the phloem sap of sweet orange

Abstract: Currently, the global citrus production is declining due to the spread of Huanglongbing (HLB). HLB, otherwise known as citrus greening, is caused by Candidatus Liberibacter asiaticus (CLas) and is transmitted by the Asian citrus psyllids (ACP), Diaphorina citri Kuwayama. ACP transmits CLas bacterium while feeding on the citrus phloem sap. Multiplication of CLas in the phloem of citrus indicates that the sap contains all the essential nutrients needed for CLas. In this study, we investigated the micro-and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…Second, these difference may be a strategic change in the psyllid wherein phloem ingestion is elevated on flush, in preparation for reproduction, while greatly reduced on mature leaves where the psyllid only needs to survive until flush is present. Third, the reduced nutritive content of phloem fluids in mature leaves could be a form of host plant resistance, as was demonstrated in a resistant sugarcane cultivar (Akbar et al 2014 ; Hijaz et al 2016 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, these difference may be a strategic change in the psyllid wherein phloem ingestion is elevated on flush, in preparation for reproduction, while greatly reduced on mature leaves where the psyllid only needs to survive until flush is present. Third, the reduced nutritive content of phloem fluids in mature leaves could be a form of host plant resistance, as was demonstrated in a resistant sugarcane cultivar (Akbar et al 2014 ; Hijaz et al 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…Of these factors, nutrition may be especially important. The general conclusion of several recent papers (Hijaz et al 2016 ; Killiny 2017 ; Setamou et al 2016 ; Valim and Killiny 2017 ) is that the nutritional composition of phloem changes depending on the species, cultivar, and the age of the plant tissues. Based on this literature, we can conclude that there were nutritional differences between immature and mature leaves in our experiment, and similar experiments by others (George et al 2017 ; Luo et al 2015 ), as well as nutritional differences due to host species and cultivar used in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoric acid is found at high level in the haemolymph. Phosphoric acid is reported in the haemolymph of honey bee (Aliferis et al ., ) and the phloem sap of many plants, including citrus (Dinant et al ., ; Hijaz et al ., ). Besides phosphoric acid, many organic acids are detected in the haemolymph.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, many sugar nucleotides such as UDP‐G and GDP‐G are detected in plant tissues (Nieman & Clark, ). ATP, ADP, AMP, GTP and GMP, NAD, NADP, riboflavin 5′‐phosphate sodium salt hydrate (FMN), FAD and riboflavin are reported recently as being detected in tissue of citrus phloem sap (Hijaz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, in a characterization of the composition of the phloem sap of Citrus sinensis (var. pineapple sweet orange), it was found that the phloem sap is rich in flavonoids, hydroxycinnamates, nucleotides, macro- and micro-nutrients [ 16 ]. The most abundant macro-nutrients were calcium and magnesium, whereas the most abundant micro-nutrients were zinc and manganese [ 16 ].…”
Section: Introductionmentioning
confidence: 99%